The Literature and Cultural Ecology of Imperial Examinations in the Ming Dynasty - Chen, Wenxin (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
The book examines the relationship between imperial examinations and literature from the perspective of restoring the cultural ecology of imperial examinations in Ming China, breaking through the paradigm of pure literature research.This book presents an important practice in adjusting the pattern of literary research. The contents of this book include five mutually independent but supportive parts: 1) the living conditions and careers of the literary attendants; 2) the educational background and school's consciousness of the Ming literati; 3) top candidates and Ming literature; 4) genres of imperial examination and the Ming society; 5) exam cheating cases from the perspective of politics and literature. This book will appeal to readers interested in Chinese literature and culture and the imperial examination system in ancient China. CHEN Wenxin, Professor of Chinese Literature at Wuhan University in China, is currently the chairman of the Professor Committee of the College of Chinese Language and Literature and the director of the Academic Committee of the Chinese Traditional Culture Research Centre of Wuhan University. As the chief editor of the 18-volume Chinese Literary Chronicle, he has won the first Chinese Government Award for Publishing.
Chapter 1. The Living Conditions and Literary Careers of the Hanlin Literati in the Ming Dynasty -- Chapter 2. The Background of the Imperial Examination and the School Consciousness of the Ming Literati -- Chapter 3. Zhuangyuan and Literature in the Ming Dynasty -- Chapter 4. Writing Styles of the Imperial Examination and Ming Society -- Chapter 5. Exam Cheating Cases from the Perspective of Ming Politics and Literature. .
Keywords: Oriental literature; Classical literature; Literature, Ancient; China -- History; Ethnology -- Asia; Culture; Education and state; Asian Literature; Classical and Antique Literature; History of China; Asian Culture; Educational Policy and Politics